Rationale and clinical utility of the darunavir–cobicistat combination in the treatment of HIV/AIDS - Putcharoen O (Drug Design, Development and Therapy, 2015)
Opass Putcharoen,1 Tanya Do,2 Anchalee Avihingsanon,2 Kiat Ruxrungtham1,2 1Department of Medicine, Faculty of Medicine, Chulalongkorn University, 2The HIV Netherlands Australia Thailand (HIV-NAT) Research Collaboration, The Thai Red Cross AIDS Research Center, Bangkok, Thailand Abstract: This article is to provide an update overview of cobicistat (COBI)-boosted darunavir in response to its recent approval by the US Food and Drug Administration, and inclusion as an alternative first-line regime in the 2015 treatment guidelines in the US. COBI is a relatively new non-antiretroviral cytochrome P450 3A inhibitor or pharmacoenhancer. The rationale behind COBI development was to provide an alternative to ritonavir (RTV) as a protease inhibitor pharmacoenhancer, due to associated adverse events with short- and long-term RTV use, such as gastrointestinal intolerability, drug–drug interactions, insulin resistance, lipodystrophy, and hyperlipidemia. Although in vitro studies suggest that COBI may result in a lower incidence of undesired drug–drug interactions and lipid-associated disorders than RTV, not all Phase III studies have well addressed these issues, and the data are limited. However, Phase III studies have demonstrated tolerability, noninferiority, and bioequivalence of COBI compared to RTV. Two main advantages of COBI over RTV-containing regimes have been noted as follows: 1) COBI has no anti-HIV activity; therefore, resistance to COBI as a booster in addition to protease inhibitor resistance is of little concern, allowing for COBI-containing regimes in future. 2) COBI’s solubility and dissolution rate allow for co-formulated/fixed-dose combination products. Nonetheless, prior to initiating COBI-containing treatment regimens, the following should be considered: 1) COBI may increase serum creatinine levels and reduce estimated glomerular filtration rate (GFR) without affecting actual GFR; 2) potential drug–drug interaction data are insufficient, warranting caution when initiating COBI in conjunction with concomitant medication or in individuals with multiple comorbidities; 3) food plays a pivotal role in boosting darunavir exposure, warranting caution and patient education on the importance of taking COBI-containing regimens with appropriate amounts of food; and 4) data on the success of COBI-containing regimens in treatment-experienced patients are limited. Keywords: first-line regime, pharmacoenhancer, adverse events, ritonavir, drug–drug interactions, tolerability